Penerapan Strategi Pembelajaran Peningkatan Kemampuan Berpikir (SPPKB) Pada Pembelajaran Matematika Peserta Didik Kelas VII SMPN 28 Padang - Musdi, Edwin; Anggrawati, Ari (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The purpose of this research are: 1) to describe the learning activities of learners with the application of Learning Strategy of Improving Thinking Ability (SPPKB) at class VII SMPN 28 Padang academic year 2017/2018, and 2) to know the ability of mathematical connections of learners who were taught by Learning Strategy Improvement Thinking Ability (SPPKB) in class VII SMPN 28 Padang academic year 2017/2018. This type of research was a quasy-experiment with a Randomized Control only Group Design study. Data collection techniques were using observation sheets to see learners' activities and written tests to see the mathematical connections of learners. Based on the results showed that 1) the learning activities of the students increased with the average percentage (75%), (65%), (28%), (45%) and (77%). 2) the ability of mathematical connections of learners who were taught with SPPKB was higher than the ability of mathematical connections of learners who were not taught with SPPKB on class VII SMPN 28 Padang Lesson Year 2017/2018. Keywords: activities, the ability of mathematical connections, SPPKB.